1995
DOI: 10.1002/pen.760350902
|View full text |Cite
|
Sign up to set email alerts
|

Master curve approach to polymer crystallization kinetics

Abstract: Nonisothermal crystallization kinetic data obtained from differential scanning calorimetry (DSC) for a poly(ethylene terephthalate) are corrected for the effects of temperature lag between the DSC sample and furnace using the method of Eder and Janeschitz‐Kriegl which is based on experimental data alone without resort to any kinetic model. A method is presented for shifting the corrected nonisothermal crystallization kinetic data with respect to an arbitrarily chosen reference temperature to obtain a master cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 8 publications
1
40
0
14
Order By: Relevance
“…Otherwise, (dθ/dt) t = 0 will be zero and θ t + Δt will always be zero, as clearly demonstrated by Galera et al [8]. They showed that θ t = 0 equal to 10 -3 was a good value to be used instead of 10 -14 suggested by Chan [10]. Therefore in the present study it was tested 10 -3 , 10 -4 and 10 -14 as the initial crystallinity in the Nakamura's model.…”
Section: Figurementioning
confidence: 84%
See 1 more Smart Citation
“…Otherwise, (dθ/dt) t = 0 will be zero and θ t + Δt will always be zero, as clearly demonstrated by Galera et al [8]. They showed that θ t = 0 equal to 10 -3 was a good value to be used instead of 10 -14 suggested by Chan [10]. Therefore in the present study it was tested 10 -3 , 10 -4 and 10 -14 as the initial crystallinity in the Nakamura's model.…”
Section: Figurementioning
confidence: 84%
“…About 3.0 mg of the material, sealed in an aluminum pan, was heated to 200°C and held at this temperature for 5 minutes before cooling at different rates (50, 40, 30, 20, 10 and 5 °C/min) to 30°C under nitrogen atmosphere. According the procedure recommended by Isayev et al [10][11][12] the experiments were carried out with the same sample for all the six cooling rates in order to obtain good repeatability for the heat transfer conditions between DSC furnace and the aluminum pan.…”
Section: Methodsmentioning
confidence: 99%
“…Os dados de K(T) versus T podem então ser ajustados a uma equação do tipo Hoffman & Lauritzen [8,14] representada pela equação 10:…”
Section: Método Da Curva Mestre Aplicado à Cristalizaçãounclassified
“…Entretanto, como já mencionado, estes experimentos isotérmicos só são possíveis em temperaturas mais elevadas, em condições bem distantes das observadas nas cristalizações em condições de processamento, sendo necessária grande extrapolação. Assim, para diminuir a extensão desta extrapolação, Isayev et al [8] propuseram o método da Curva Mestre ("Master Curve Approach") para determinar a constante cinética de cristalização não-isotérmica, K(T). Este método emprega experimentos de cristalização não-isotérmica obtidos por Calorimetria Exploratória Diferencial, DSC, a diferentes taxas de resfriamento, permitindo a obtenção dos parâmetros cinéticos em temperaturas mais baixas que os experimentos isotérmicos.…”
Section: Introductionunclassified
“…Classical polynomial or purely phenomenological models such as Isayev model [3] widely used for reticulation modeling fail to address correctly the main phenomena of sulphur vulcanization, i.e., induction time, acceleration of cross-linking, and reversion. The reason is that such models do not rely on any chemical consideration.…”
Section: Chemical Modeling Of Sulphur Vulcanizationmentioning
confidence: 99%